Pelatihan pembinaan UMKM berbasis Teknologi Informasi untuk meningkatkan SDM pelaku UMKM - Mahpuz Mahpuz; Hariman Bahtiar; Fathurahman Fathurahman; Amri Muliawan Nur (Universitas Hamzanwadi, 2021)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia are currently one of the business sectors that can assist the government in employing the community. The Indonesian government, in its policies, has allocated many funds to increase the interest of the millennial generation in the field of entrepreneurship, especially various types of technology-based businesses such as startups, so that the Indonesian economy is growing. This training activity for assisting MSME actors aims to improve the ability of MSME actors ability to develop their business through information technology assistance. Improve knowledge of financial management and e-commerce for MSME actors and mastery of Information Technology for MSME actors. The participants came from 3 sub-districts in East Lombok Regency, namely Sukamulia, Selong, and Labuan Haji. The MSME coaching training involved 100 MSME participants in 3 sub-districts. MSME actors are given an understanding of the use of e-commerce and the importance of using technology in developing MSME products to increase their income. Implementing this activity is by practicing using various available promotional platforms, such as YouTube, Instagram, and Google Business. The results obtained are that MSME actors can master the basics of using the promotion platform that has been taught.